A process for the large-scale production of compression-resistant biomass-based microspheres

CN122958760APending Publication Date: 2026-10-23HUNAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611176250.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0008]本发明旨在解决现有技术中制备生物质基微球力学性能较差,难以规模化制备的缺陷,开发一种通用性的规模化制备工艺

Benefits of technology

(1)采用多孔高强度硅-氧微球模板进行生物质沉积-交联的反向合成路径;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958760A_ABST
    Figure CN122958760A_ABST
Patent Text Reader

Abstract

The application provides a large-scale preparation process of compression-resistant biomass-based microspheres. Silicon-oxygen porous microspheres generated in situ are used as a skeleton, after surface modification, water-soluble biomass polysaccharides are induced to self-deposit on the surface of the template, and the target microspheres are prepared through in-situ solidification. The obtained microspheres have excellent mechanical properties and biocompatibility. The method has strong universality and can be adapted to various biomass polysaccharide systems, and provides a simple and universal preparation method for different characteristics of biomedical microsphere carriers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical microsphere preparation, and more specifically, to a general process for the large-scale production of biomass-based microspheres with different particle sizes, compression resistance, and drug loading capabilities. Background Technology

[0002] Biomass-based microspheres, as a type of functional polymer material, have shown broad application prospects in fields such as biomedicine, tissue engineering, drug sustained release, cell culture, and separation and purification due to their excellent biocompatibility, biodegradability, and unique three-dimensional network structure. In particular, gel microspheres prepared from natural polysaccharides such as chitosan, alginate, and cellulose derivatives have become a research hotspot in the field of biomaterials in recent years due to their wide availability, environmental friendliness, and extracellular matrix-like structural characteristics.

[0003] In biomedical applications, microspheres are frequently used as drug delivery carriers or cell culture microcarriers. Their performance is highly dependent on the microspheres' mechanical strength, particle size uniformity, pore structure, and surface chemical properties. For example, in injectable tissue repair materials, microspheres need sufficient compressive strength and toughness to withstand the pressure of the in vivo mechanical environment without breaking; in cell expansion culture, microspheres need suitable pore size and surface reaction sites to support cell adhesion and proliferation. However, existing methods for preparing biomass-based gel microspheres still have significant shortcomings.

[0004] Currently, commonly used methods for preparing microspheres mainly include emulsion crosslinking, spray drying, and extrusion coagulation. Although emulsion crosslinking is simple to operate, the resulting microspheres have a wide particle size distribution and poor reproducibility. Spray drying can achieve continuous production, but it causes significant damage to heat-sensitive bioactive substances, and the pore structure of the microspheres is difficult to control precisely. Extrusion coagulation relies heavily on microfluidic chips or nozzle devices, resulting in low production efficiency and making it difficult to achieve industrial-scale production.

[0005] More importantly, biomass-based microspheres prepared by traditional methods generally suffer from insufficient mechanical properties. Due to the low rigidity and limited cross-linking density of natural polysaccharide molecular chains, the resulting microspheres often exhibit poor strength in the swollen state, making them prone to rupture during stirring, transportation, or in vivo implantation. To address this challenge, researchers have attempted to improve the mechanical properties of microspheres through chemical cross-linking, nanocompositing, or blending modification. However, these methods often require the introduction of synthetic polymers or nanofillers, which may affect the biocompatibility and degradation behavior of the materials. Furthermore, existing modification methods primarily focus on optimizing the internal structure of the microspheres, with limited ability to synergistically regulate the surface and internal pore structure, making it difficult to achieve a balance between high porosity and high strength.

[0006] In recent years, template methods have attracted widespread attention due to their advantages in controlling microsphere particle size and pore structure. By selecting appropriate template materials, a regular pore network can be constructed inside microspheres, which can then be endowed with specific chemical properties through subsequent functionalization modifications. However, traditional inorganic or synthetic polymer templates are often difficult to remove completely, and non-biocompatible templates may trigger immune responses.

[0007] To address the aforementioned technical bottlenecks, developing a preparation process that can adapt to different biomass raw materials for spheroidization, ensuring the spheres possess compressibility, compression resilience, good biocompatibility, and uniform particle size, while enabling large-scale, one-time production, has become a pressing technical problem in this field. This invention, based on the template method and reactive self-assembly principle, constructs modified silica-oxygen porous microspheres as a framework, combined with in-situ cross-linking reactions of reactive encapsulants and biomass polysaccharides, achieving control over microsphere particle size, porosity, and surface chemical properties. This method provides a new approach for the large-scale preparation of high-performance biomass-based gel microspheres and is expected to promote their widespread application in the biomedical field. Summary of the Invention

[0008] The present invention aims to address the shortcomings of existing technologies in preparing biomass-based microspheres, which have poor mechanical properties and are difficult to prepare on a large scale, and to develop a universal large-scale preparation process.

[0009] The objective of this invention is achieved through the following technical solution: A large-scale preparation process for compression-resistant biomass-based microspheres includes the following steps: I: Preparation of silicon-oxygen porous microspheres: Prepare an aqueous solution containing tetramethoxysilane and polyethylene glycol. Add the aqueous solution and surfactant to an organic solvent and heat at 20-35°C. o At temperature C, the mixture is stirred at a speed of 250-500 rpm to form water-in-oil microspheres in an organic solvent. Then, an acid solution is gradually added dropwise to the organic solvent. Stirring is maintained for 1-2 hours to form silicon-oxygen porous microspheres through hydrolysis, which are then filtered. In the aqueous solution, the mass concentration of tetramethoxysilane is between 3-6%, the mass concentration of polyethylene glycol is between 8-12%, the volume of the aqueous solution is between 15-20% of the organic solvent, the mass of the surfactant is between 1.5-2.5% of the aqueous solution, and the pH value of the acid solution is between 3-4, and the volume is between 6-10% of the aqueous solution. II: Preparation of hydroxylated porous microspheres: The filtered silicon-oxygen porous microspheres were washed alternately with ethanol and pure water to remove organic solvents and polyethylene glycol; the washed and dried silicon-oxygen porous microspheres were added to a NaOH aqueous solution with a molar concentration of 3-5 mol / L, heated and stirred at 60-80℃ for 0.5-1.5 hours, the solid microspheres were collected by centrifugation, washed with deionized water until neutral, and then dispersed in dilute hydrochloric acid with pH 2-4 for 30-60 minutes. The microspheres were then filtered out and repeatedly washed with water to remove residual ions. The microspheres were dried at a temperature below 60℃ to obtain hydroxylated porous microspheres. The volumes of NaOH aqueous solution and dilute hydrochloric acid used were between 10 and 20 times the volume of the microspheres; the surface hydroxyl value of the hydroxylated porous microspheres was between 3 and 6 mmol / g. III: Preparation of Aldehyde-Tylated Porous Microspheres: Prepare an anhydrous ethanol solution of trimethoxypropionaldehyde silane with a volume concentration between 0.5% and 2%. Adjust the pH to 4.0-5.0 with glacial acetic acid and stir at room temperature for 15-30 minutes. Then, add the dried hydroxylated porous microspheres into the solution and soak at 15-25°C for 30-60 minutes. Filter the microspheres and gently rinse them with anhydrous ethanol to remove the reaction monomers. Dry them with nitrogen and let them stand at room temperature for 12-24 hours under nitrogen protection. Then heat the solution to 100-115°C and let it stand for another 15-25 minutes to obtain aldehyde-tylated porous microspheres. The volume of the anhydrous ethanol solution of trimethoxypropionaldehyde silane is 12-20 times the volume of the hydroxylated porous microspheres. The aldehyde group value on the surface of the aldehyde-tylated porous microspheres is between 1.5-3 mmol / g. IV: Self-assembly of biomass-based microspheres: Prepare a 5-10% (w / w) aqueous solution of biomass polysaccharides. Adjust the pH to 4.0-5.0 by adding glacial acetic acid. Add aldehyde-modified porous microspheres to the solution and incubate at 25-40°C. o Stir at 150-300 rpm for 2-4 hours under temperature C, and filter to obtain initially assembled microspheres; wherein, the volume of biomass polysaccharide aqueous solution added is between 6-10 times the volume of the microspheres; V: Solidification of biomass-based microspheres: The initially assembled microspheres are placed in acetone and stirred at 250-400 rpm to disperse them evenly. Glacial acetic acid is added to adjust the pH of the system to between 4.0 and 5.0. Then, a small molecule aldehyde aqueous solution is slowly added dropwise and stirring is continued for 1.5-3 hours. After the reaction is complete, the microspheres are filtered out, washed repeatedly with pure water, and dried at 30-60℃ to obtain the final microsphere product. The volume ratio of the initially assembled microspheres to acetone is between 1:5 and 1:10, the volume of the aqueous solution of small molecule aldehydes is between 5% and 10% of the volume of acetone, and the mass concentration of small molecule aldehydes is between 3% and 6%.

[0010] Furthermore, the acid solution is an aqueous solution of hydrochloric acid, oxalic acid, acetic acid, or sulfuric acid.

[0011] Furthermore, the organic solvent is one of cyclohexane, cyclohexanone, octane, liquid paraffin, and isopropyl palmitate.

[0012] Furthermore, the surfactant is one of span80, tween20, and glyceryl monooleate.

[0013] Furthermore, the tetramethoxysilane (TMOS) undergoes hydrolysis and condensation under acidic conditions to first form silanol and methanol, and the silanol further condenses to form a polysiloxane backbone.

[0014] Furthermore, the polyethylene glycol has a molecular weight between 200 and 600, and acts as a further pore-forming agent in the microspheres to improve the porosity of the silicon-oxygen porous microspheres.

[0015] Furthermore, the trimethoxypropionaldehyde silane is alcoholyzed in anhydrous ethanol to generate an unstable silanol intermediate (-Si(OH)3), which then undergoes dehydration condensation with hydroxyl groups on the surface of the microspheres to form stable Si-O-Si covalent bonds, thereby introducing the aldehyde group in the molecule into the microspheres.

[0016] Furthermore, the biomass polysaccharide is a water-soluble biomass polysaccharide with amino groups and its derivatives, such as chitosan, carboxymethyl chitosan, amino-modified hyaluronic acid, amino-modified dextran, and amino acids; the amino groups on the biomass can react with aldehyde groups to achieve cross-linking.

[0017] in, The molecular formula of carboxymethyl chitosan is:

[0018] The degree of substitution of carboxymethyl groups, calculated based on the proportion of substituted ethyl hydroxyl groups, ranges from 0.4 to 0.8. The molecular formula of amino-modified hyaluronic acid is:

[0019] The substitution of amino groups is calculated based on the proportion of the substituted acyl hydroxyl groups, ranging from 0.3 to 0.8. The molecular formula of amino-modified dextran is:

[0020] The degree of substitution of the amino group, calculated based on the proportion of substituted ethyl hydroxyl groups, ranges from 0.4 to 0.8. Furthermore, the porous microspheres have a particle size between 100-600 μm and a porosity between 45-75%.

[0021] Furthermore, the amino groups on the biomass polysaccharide molecular chain and the aldehyde groups on the surface of the microspheres form Schiff bases (-C=N-) through a condensation reaction, thereby achieving chemical anchoring and self-assembly of the polysaccharide on the surface of the microspheres.

[0022] Furthermore, the biomass polysaccharide loading in the biomass-based microspheres is between 150-300 mg / g.

[0023] Furthermore, the small molecule aldehyde is one of glutaraldehyde and glyoxal. The glyoxal slowly penetrates into the microspheres in the solution to promote further cross-linking and solidification of the biomass polysaccharides in the microspheres, thereby enhancing the structural integrity of the biomass layer.

[0024] Furthermore, the biomass-based microspheres can be loaded with drugs by soaking in a water-soluble drug solution; preferably, the prepared microspheres can be immersed in a drug aqueous solution with a concentration of 5-10% to achieve adsorption loading of drugs of different concentrations.

[0025] Furthermore, the drug is preferably a water-soluble drug.

[0026] Furthermore, the particle size of the biomass-based microspheres increases by 2-15% before and after loading with biomass polysaccharides, while the particle size remains basically stable.

[0027] Furthermore, the biomass-based microspheres can achieve complete rebound and shape recovery after the pressure is released before being subjected to extreme compression that could destroy the sphere.

[0028] Furthermore, the advantages of the large-scale preparation process of the compression-resistant biomass-based gel microspheres are: (1) A reverse synthesis route of biomass deposition-crosslinking using porous high-strength silicon-oxygen microsphere templates; (2) A silicon-oxygen microsphere framework is obtained by hydrolysis of silicon-oxygen precursors, which can be modified to load hydroxyl and aldehyde groups, thereby providing sufficient anchoring sites for biomass polysaccharide macromolecules. (3) Since this method uses a silicon-oxygen sphere template skeleton that is easier to shape, except for the first step which is the sphere forming step, all other steps are carried out by the immersion reaction self-assembly mechanism, which can ensure that the particle size can be stabilized in the early stage, and thus make it easier to control the particle size of the microspheres. (4) The silicon-oxygen framework of the microspheres can provide the microspheres with good compressive strength and mechanical properties; (5) Since the process of TMOS hydrolysis to form silicon-oxygen microsphere framework is very stable, the subsequent modification process after solidification of the sphere is relatively simple and the conditions are mild, and there is little mutual interference. Therefore, the preparation of biomass-based microspheres can be carried out in batches after the preparation of microsphere framework.

[0029] Furthermore, the performance testing method for the microspheres is as follows: I: Particle size testing: SEM observation; II: Mechanical properties: The compressive strength and modulus of the microspheres were tested using a mechanical testing instrument in compression mode. III: Biomass polysaccharide loading: Thermogravimetric analysis of microspheres at 500°C o The difference between the residual mass after C and the original mass of the microspheres; IV: Hydroxyl value: The hydroxyl value of the microspheres was tested according to the test method described in Chinese authorized invention patent CN116242960B; V: Aldehyde value: Measured using the hydroxylamine hydrochloride-potential titration conductivity method: Hydroxylamine hydrochloride is added to a microsphere dispersion of a certain volume concentration, HCl is released through the reaction, and then titrated with NaOH. The amount of HCl is determined based on the change in conductivity, and thus the amount of aldehyde is determined. VI: Porosity: The porosimetry method was tested using a mercury porosimetry instrument; VII: Drug loading concentration and release test: Drug loading was achieved by immersing the microspheres in a drug solution at room temperature for 24 hours and measuring the concentration difference of the drug solution before and after the immersion to obtain the amount of absorbed drug; Drug release was achieved by immersing the drug-loaded microspheres in PBS solution and measuring the drug concentration in the solution; Drug concentration was tested using the ultraviolet spectroscopy characteristic peak method. Attached Figure Description

[0030] Figure 1 The image shows the internal micrograph of the silicon-oxygen porous microspheres prepared in Example 1 after freeze-drying. Figure 2 The image shows the TGA pattern of the final microspheres prepared in Example 1. Figure 3 SEM image of the final microspheres prepared in batches according to the process of Example 1; Figure 4 This is a partial SEM image of the final microspheres prepared in Example 1 after being cut open; Figure 5 This is a schematic diagram of the compression of the final microspheres prepared in Example 1; Figure 6 The image shows the drug release concentration curve after the final microspheres prepared in Example 1 are loaded with the drug. Detailed Implementation

[0031] To make the technical solutions of this disclosure clearer and easier to understand, the formulations, preparation methods, and properties provided in this disclosure are described in detail below with reference to the accompanying drawings and specific embodiments. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods. Unless otherwise specified, the materials and reagents used in the following embodiments are commercially available.

[0032] Example 1 A large-scale preparation process for compression-resistant biomass-based microspheres includes the following steps: I: Preparation of silicon-oxygen porous microspheres: An aqueous solution containing tetramethoxysilane and polyethylene glycol was prepared. The aqueous solution and surfactant were added to an organic solvent and heated to 25°C. o At C, the mixture was stirred at 400 rpm to form water-in-oil microspheres in an organic solvent. Then, an acid solution was gradually added dropwise to the organic solvent. Stirring was maintained for 1.5 h to allow the hydrolysis reaction to form silicon-oxygen porous microspheres, which were then filtered. In the aqueous solution, the mass concentration of tetramethoxysilane is 4.5%, and the mass concentration of polyethylene glycol is 9.5%; the volume of the aqueous solution is 16% of the organic solvent, and the mass of the surfactant is 2.2% of the aqueous solution; the pH value of the acid solution is 3.5, and the volume is 8% of the aqueous solution. II: Preparation of hydroxylated porous microspheres: The filtered silicon-oxygen porous microspheres were washed alternately with ethanol and pure water to remove organic solvents and polyethylene glycol; the washed and dried silicon-oxygen porous microspheres were added to a 3.5 mol / L NaOH aqueous solution, heated and stirred at 70°C for 1 hour, the solid microspheres were collected by centrifugation, washed with deionized water until neutral, and then dispersed in dilute hydrochloric acid at pH=3 for 45 minutes. The microspheres were then filtered out and repeatedly washed with water to remove residual ions. The microspheres were dried at a temperature below 45°C to obtain hydroxylated porous microspheres. The volume of the NaOH aqueous solution used was 15 times the volume of the microspheres; the volume of the dilute hydrochloric acid used was 12 times the volume of the microspheres; and the surface hydroxyl value of the hydroxylated porous microspheres was 4.2 mmol / g. III: Preparation of Aldehyde-Tylated Porous Microspheres: An anhydrous ethanol solution of trimethoxypropionaldehyde silane with a volume concentration of 1.2% was prepared. Glacial acetic acid was added to adjust the pH to 4.5, and the mixture was stirred at room temperature for 20 minutes. The dried hydroxylated porous microspheres were then added to the solution, and the temperature was controlled at 20°C for 40 minutes. The microspheres were filtered out and gently rinsed with anhydrous ethanol to remove the reaction monomers. They were then dried with nitrogen and allowed to stand at room temperature for 18 hours under nitrogen protection. After standing for another 20 minutes, the solution was heated to 105°C and the microspheres were removed to obtain aldehyde-tylated porous microspheres. The volume of the anhydrous ethanol solution of trimethoxypropionaldehyde silane was approximately 15 times the volume of the hydroxylated porous microspheres. The aldehyde group value on the surface of the aldehyde-tylated porous microspheres was 1.8 mmol / g. IV: Self-assembly of biomass-based microspheres: A 7.5% (w / w) aqueous solution of biomass polysaccharides was prepared. Glacial acetic acid was added to the solution to adjust the pH to 4.5. Aldehyde-modified porous microspheres were then added to the solution and incubated at 32°C. o The mixture was stirred at 200 rpm for 3 hours under temperature C, and the initial assembled microspheres were obtained by filtration. The volume of the added biomass polysaccharide aqueous solution was 8 times the volume of the microspheres. V: Solidification of biomass-based microspheres: The initially assembled microspheres were put into acetone and stirred at 320 rpm to disperse them evenly. Glacial acetic acid was added to adjust the pH of the system to 4.5. Then, a small molecule aldehyde aqueous solution was slowly added dropwise and stirred for 2 hours. After the reaction was completed, the microspheres were filtered out, washed repeatedly with pure water, and dried at 40°C to obtain the final microsphere product. The volume ratio of the initially assembled microspheres to acetone was 1:8, the volume of the small molecule aldehyde aqueous solution was 7% of the volume of acetone, and the mass concentration of the small molecule aldehyde was 4%.

[0033] The molecular weight of the polyethylene glycol is 400.

[0034] The acid solution is an aqueous solution of hydrochloric acid.

[0035] The organic solvent is octane.

[0036] The surfactant is Tween20.

[0037] The small molecule aldehyde is glutaraldehyde.

[0038] The biomass polysaccharide is amino-modified hyaluronic acid, with the amino groups substituted at a ratio of 0.45 based on the substituted acyl hydroxyl groups. It is a commercially available product.

[0039] The porous microspheres have a particle size between 150-200 μm and a porosity of 58%. Figure 1 As shown, the micrographs of the freeze-dried porous microspheres reveal a clear framework and numerous pores.

[0040] like Figure 2 As shown in the TGA curve, the biomass polysaccharide loading in the microspheres is 221.2 mg / g, calculated based on the weight loss at 500 °C.

[0041] The final microsphere product has a particle size between 160-220 μm, such as Figure 3 As shown, in the mass production of 100g microspheres, the final microsphere product has good morphology and relatively uniform particle size; as Figure 4 As shown, a relatively dense layer of biomass is deposited on the surface of the microspheres, and some of the internal pores are also deposited.

[0042] The final microsphere product has a compression limit deformation of 74% and a compression modulus of 0.92 MPa. As shown in Figure 5, the microspheres retain a good shape even after being compressed and released.

[0043] When the prepared microspheres were immersed in a 10 mg / ml solution of doxorubicin hydrochloride for 24 hours at room temperature, the solution was in significant excess, and the drug concentration reached 44 mg / ml (based on the microsphere volume). Then, the microspheres were immersed in PBS solution at room temperature. Figure 6As shown, the drug release exhibits a significant burst release phenomenon, with a sustained release time of approximately 20 days and a release rate of up to 93%.

[0044] Example 2 A large-scale preparation process for compression-resistant biomass-based microspheres includes the following steps: I: Preparation of silicon-oxygen porous microspheres: An aqueous solution containing tetramethoxysilane and polyethylene glycol was prepared. The aqueous solution and surfactant were added to an organic solvent and heated at 30°C. o At C, the mixture was stirred at 450 rpm to form water-in-oil microspheres in an organic solvent. Then, an acid solution was gradually added dropwise to the organic solvent. Stirring was maintained for 1.8 h to allow the hydrolysis reaction to form silicon-oxygen porous microspheres, which were then filtered. In the aqueous solution, the mass concentration of tetramethoxysilane is 5%, and the mass concentration of polyethylene glycol is 10.5%; the volume of the aqueous solution is 18% of the organic solvent, and the mass of the surfactant is 2.0% of the aqueous solution; the pH value of the acid solution is 3, and the volume is 10% of the aqueous solution. II: Preparation of hydroxylated porous microspheres: The filtered silicon-oxygen porous microspheres were washed alternately with ethanol and pure water to remove organic solvents and polyethylene glycol; the washed and dried silicon-oxygen porous microspheres were added to a NaOH aqueous solution with a molar concentration of 4 mol / L, heated and stirred at 75°C for 0.8 hours, the solid microspheres were collected by centrifugation, washed with deionized water until neutral, and then dispersed in dilute hydrochloric acid with pH=3.5 for 50 minutes. The microspheres were then filtered out and repeatedly washed with water to remove residual ions, and dried at 40°C to obtain hydroxylated porous microspheres; The volume of the NaOH aqueous solution used was 12 times the volume of the microspheres; the volume of the dilute hydrochloric acid used was 10 times the volume of the microspheres; and the surface hydroxyl value of the hydroxylated porous microspheres was 3.2 mmol / g. III: Preparation of Aldehyde-Tylated Porous Microspheres: An anhydrous ethanol solution of trimethoxypropionaldehyde silane with a volume concentration of 1.6% was prepared. Glacial acetic acid was added to adjust the pH to 4.2, and the mixture was stirred at room temperature for 25 minutes. The dried hydroxylated porous microspheres were then added to the solution, and the temperature was controlled at 22°C for 50 minutes. The microspheres were filtered out and gently rinsed with anhydrous ethanol to remove the reaction monomers. They were then dried with nitrogen and allowed to stand at room temperature for 20 hours under nitrogen protection. After standing for another 22 minutes, the temperature was raised to 110°C, and the microspheres were obtained. The volume of the anhydrous ethanol solution of trimethoxypropionaldehyde silane was approximately 16 times the volume of the hydroxylated porous microspheres. The aldehyde group value on the surface of the aldehyde-tylated porous microspheres was 1.6 mmol / g. IV: Self-assembly of biomass-based microspheres: A 9.8% (w / w) aqueous solution of biomass polysaccharides was prepared. Glacial acetic acid was added to the solution to adjust the pH to 4.8. Aldehyde-modified porous microspheres were then added to the solution and incubated at 35°C. oThe mixture was stirred at 250 rpm for 3.5 hours under temperature C, and the initial assembled microspheres were obtained by filtration. The volume of the added biomass polysaccharide aqueous solution was 8.5 times the volume of the microspheres. V: Solidification of biomass-based microspheres: The initially assembled microspheres were placed in acetone and stirred at 320 rpm to disperse them evenly. Glacial acetic acid was added to adjust the pH of the system to 4.5. Then, a small molecule aldehyde aqueous solution was slowly added dropwise and stirred for 2.5 hours. After the reaction was completed, the microspheres were filtered out, washed repeatedly with pure water, and dried at 45°C to obtain the final microsphere product. The volume ratio of the initially assembled microspheres to acetone was 1:7, the volume of the small molecule aldehyde aqueous solution was 8.5% of the volume of acetone, and the mass concentration of the small molecule aldehyde was 3.5%.

[0045] The molecular weight of the polyethylene glycol is 200.

[0046] The acid solution is an aqueous solution of acetic acid.

[0047] The organic solvent is cyclohexane.

[0048] The surfactant is Span80.

[0049] The biomass polysaccharide is carboxymethyl chitosan, with a degree of substitution of 0.6 based on the proportion of substituted ethyl hydroxyl groups, and is a commercially available product.

[0050] The biomass polysaccharide is chitosan, a commercially available product.

[0051] The porous microspheres have a particle size between 120-160 μm and a porosity of 66%.

[0052] The biomass polysaccharide loading in the microspheres is 246.7 mg / g.

[0053] The small molecule aldehyde is glutaraldehyde.

[0054] The final microsphere product has a particle size between 140 and 180 μm.

[0055] The final microsphere product has a compressive limit deformation of 68% and a compressive modulus of 0.98 MPa.

[0056] The prepared microspheres were immersed in a 10 mg / ml 5-fluorouracil aqueous solution at room temperature for 24 h with a significant excess of solution, resulting in a drug loading concentration of 28 mg / ml on the microspheres (based on the microsphere volume). The microspheres were then immersed in PBS solution at room temperature, and the release time was 9 days, with a release rate of 84%.

[0057] Example 3 A large-scale preparation process for compression-resistant biomass-based microspheres includes the following steps: I: Preparation of silicon-oxygen porous microspheres: An aqueous solution containing tetramethoxysilane and polyethylene glycol was prepared. The aqueous solution and surfactant were added to an organic solvent and heated at 32°C. o At C, the mixture was stirred at 360 rpm to form water-in-oil microspheres in an organic solvent. Then, an acid solution was gradually added dropwise to the organic solvent. Stirring was maintained for 2 hours to allow the hydrolysis reaction to form silicon-oxygen porous microspheres, which were then filtered. In the aqueous solution, the mass concentration of tetramethoxysilane is 5.5%, and the mass concentration of polyethylene glycol is 10.5%; the volume of the aqueous solution is 18.5% of the organic solvent, and the mass of the surfactant is 1.8% of the aqueous solution; the pH value of the acid solution is 3.2, and its volume is 7.2% of the aqueous solution. II: Preparation of hydroxylated porous microspheres: The filtered silicon-oxygen porous microspheres were washed alternately with ethanol and pure water to remove organic solvents and polyethylene glycol; the washed and dried silicon-oxygen porous microspheres were added to a NaOH aqueous solution with a molar concentration of 4.5 mol / L, heated and stirred at 65°C for 1.2 hours, the solid microspheres were collected by centrifugation, washed with deionized water until neutral, and then dispersed in dilute hydrochloric acid at pH=3.2 for 55 minutes. The microspheres were then filtered out and repeatedly washed with water to remove residual ions, and dried at 45°C to obtain hydroxylated porous microspheres; The volume of the NaOH aqueous solution used was 16 times the volume of the microspheres; the volume of the dilute hydrochloric acid used was 12 times the volume of the microspheres; and the surface hydroxyl value of the hydroxylated porous microspheres was 3.8 mmol / g. III: Preparation of Aldehyde-Tylated Porous Microspheres: An anhydrous ethanol solution of trimethoxypropionaldehyde silane with a volume concentration of 1.0% was prepared. Glacial acetic acid was added to adjust the pH to 4.4, and the mixture was stirred at room temperature for 22 minutes. The dried hydroxylated porous microspheres were then added to the solution, and the temperature was controlled at 18°C ​​for 45 minutes. The microspheres were filtered out and gently rinsed with anhydrous ethanol to remove the reaction monomers. They were then dried with nitrogen and allowed to stand at room temperature for 20 hours under nitrogen protection. After standing for another 25 minutes, the temperature was raised to 108°C, and the microspheres were obtained. The volume of the anhydrous ethanol solution of trimethoxypropionaldehyde silane was approximately 16 times the volume of the hydroxylated porous microspheres. The aldehyde group value on the surface of the aldehyde-tylated porous microspheres was 1.9 mmol / g. IV: Self-assembly of biomass-based microspheres: A 6.4% (w / w) aqueous solution of biomass polysaccharides was prepared. Glacial acetic acid was added to adjust the pH to 4.2. Aldehyde-modified porous microspheres were then added to the solution and incubated at 32°C. o The mixture was stirred at 220 rpm for 3.2 hours under temperature C, and the initial assembled microspheres were obtained by filtration. The volume of the added biomass polysaccharide aqueous solution was 9.0 times the volume of the microspheres. V: Solidification of biomass-based microspheres: The initially assembled microspheres were placed in acetone and stirred at 360 rpm to disperse them evenly. Glacial acetic acid was added to adjust the pH of the system to 4.2. Then, a small molecule aldehyde aqueous solution was slowly added dropwise and stirred for 2.2 hours. After the reaction was completed, the microspheres were filtered out, washed repeatedly with pure water, and dried at 50°C to obtain the final microsphere product. The volume ratio of the initially assembled microspheres to acetone was 1:9, the volume of the small molecule aldehyde aqueous solution was 7.8% of the volume of acetone, and the mass concentration of the small molecule aldehyde was 4.2%.

[0058] The molecular weight of the polyethylene glycol is 300.

[0059] The acid solution is an aqueous solution of oxalic acid.

[0060] The organic solvent is liquid paraffin.

[0061] The surfactant is Span80.

[0062] The biomass polysaccharide is chitosan, a commercially available product.

[0063] The porous microspheres have a particle size between 260-320 μm and a porosity of 68%.

[0064] The biomass polysaccharide loading in the microspheres is 182.3 mg / g.

[0065] The small molecule aldehyde is glyoxal.

[0066] The final microsphere product has a particle size between 280 and 340 μm.

[0067] The final microsphere product has a compressive limit deformation of 62% and a compressive modulus of 1.05 MPa.

[0068] The microspheres were immersed in a 15 mg / ml solution of doxorubicin hydrochloride at room temperature for 24 hours with a significant excess of solution, resulting in a drug loading concentration of 34 mg / ml (based on the volume of the microspheres). The microspheres were then immersed in PBS solution at room temperature, and the release time was 16 days, with a release rate of 89%.

[0069] Example 4 A large-scale preparation process for compression-resistant biomass-based microspheres includes the following steps: I: Preparation of silicon-oxygen porous microspheres: An aqueous solution containing tetramethoxysilane and polyethylene glycol was prepared. The aqueous solution and surfactant were added to an organic solvent and heated at 32°C. oAt C, the mixture was stirred at 260 rpm to form water-in-oil microspheres in an organic solvent. Then, an acid solution was gradually added dropwise to the organic solvent. Stirring was maintained for 1.5 h to allow the hydrolysis reaction to form silicon-oxygen porous microspheres, which were then filtered. In the aqueous solution, the mass concentration of tetramethoxysilane is 5.8%, and the mass concentration of polyethylene glycol is 8.5%; the volume of the aqueous solution is 18.5% of the organic solvent, and the mass of the surfactant is 2.2% of the aqueous solution; the pH value of the acid solution is 3.2, and the volume is 9.5% of the aqueous solution. II: Preparation of hydroxylated porous microspheres: The filtered silicon-oxygen porous microspheres were washed alternately with ethanol and pure water to remove organic solvents and polyethylene glycol. The washed and dried silicon-oxygen porous microspheres were added to a NaOH aqueous solution with a molar concentration of 3.3 mol / L, heated and stirred at 75°C for 1.2 hours, and the solid microspheres were collected by centrifugation. They were washed with deionized water until neutral, and then dispersed in dilute hydrochloric acid with pH=3.2 for 45 minutes. The microspheres were then filtered out and repeatedly washed with water to remove residual ions. They were dried at 45°C to obtain hydroxylated porous microspheres. The volume of NaOH aqueous solution used was 16 times the volume of the microspheres, and the volume of dilute hydrochloric acid used was also 16 times the volume of the microspheres; the surface hydroxyl value of the hydroxylated porous microspheres was 5.2 mmol / g. III: Preparation of Aldehyde-Tylated Porous Microspheres: An anhydrous ethanol solution of trimethoxypropionaldehyde silane with a volume concentration of 0.9% was prepared. Glacial acetic acid was added to adjust the pH to 4.5, and the mixture was stirred at room temperature for 16 minutes. The dried hydroxylated porous microspheres were then added to the solution, and the temperature was controlled at 18°C ​​for 35 minutes. The microspheres were filtered out and gently rinsed with anhydrous ethanol to remove the reaction monomers. They were then dried with nitrogen and allowed to stand at room temperature for 16 hours under nitrogen protection. After standing for another 16 minutes, the solution was heated to 108°C and allowed to stand for another 16 minutes to obtain aldehyde-tylated porous microspheres. The volume of the anhydrous ethanol solution of trimethoxypropionaldehyde silane was 18 times the volume of the hydroxylated porous microspheres. The aldehyde group value on the surface of the aldehyde-tylated porous microspheres was 2.2 mmol / g. IV: Self-assembly of biomass-based microspheres: A 5.5% (w / w) aqueous solution of biomass polysaccharides was prepared. Glacial acetic acid was added to the solution to adjust the pH to 4.4. Aldehyde-modified porous microspheres were then added to the solution and incubated at 28°C. o The mixture was stirred at 180 rpm for 3.2 hours under temperature C, and the initial assembled microspheres were obtained by filtration. The volume of the added biomass polysaccharide aqueous solution was 7.2 times the volume of the microspheres. V: Solidification of biomass-based microspheres: The initially assembled microspheres were placed in acetone and stirred at 280 rpm to disperse them evenly. Glacial acetic acid was added to adjust the pH of the system to 4.2. Then, a small molecule aldehyde aqueous solution was slowly added dropwise and stirred for 2.5 hours. After the reaction was completed, the microspheres were filtered out, washed repeatedly with pure water, and dried at 50°C to obtain the final microsphere product. The volume ratio of the initially assembled microspheres to acetone was 1:7.6, the volume of the small molecule aldehyde aqueous solution was 7.5% of the volume of acetone, and the mass concentration of the small molecule aldehyde was 4.0%.

[0070] The molecular weight of the polyethylene glycol is 400.

[0071] The acid solution is an aqueous solution of sulfuric acid.

[0072] The organic solvent is isopropyl palmitate.

[0073] The surfactant is Span80.

[0074] The biomass polysaccharide is amino-modified hyaluronic acid, with the amino groups substituted at a ratio of 0.52 based on the substituted acyl hydroxyl groups. It is a commercially available product.

[0075] The porous microspheres have a particle size between 420-480 μm and a porosity of 62%.

[0076] The biomass polysaccharide loading in the microspheres is 169.4 mg / g.

[0077] The small molecule aldehyde is glutaraldehyde.

[0078] The final microsphere product has a particle size between 440 and 500 μm.

[0079] The final microsphere product has a compressive limit deformation of 62% and a compressive modulus of 0.9 MPa.

[0080] The prepared microspheres were immersed in a 9 mg / ml pirarubicin hydrochloride aqueous solution at room temperature for 24 h with a significant excess of solution. The drug concentration loaded on the microspheres reached 26 mg / ml (based on the microsphere volume), and the release time was 14 days, with a release ratio of 91%.

[0081] Example 5 A large-scale preparation process for compression-resistant biomass-based microspheres includes the following steps: I: Preparation of silicon-oxygen porous microspheres: An aqueous solution containing tetramethoxysilane and polyethylene glycol was prepared. The aqueous solution and surfactant were added to an organic solvent and heated to 26°C. oAt C, the mixture was stirred at 400 rpm to form water-in-oil microspheres in an organic solvent. Then, an acid solution was gradually added dropwise to the organic solvent. Stirring was maintained for 1.8 h to allow the hydrolysis reaction to form silicon-oxygen porous microspheres, which were then filtered. In the aqueous solution, the mass concentration of tetramethoxysilane is 4.6%, and the mass concentration of polyethylene glycol is 10.4%; the volume of the aqueous solution is 15.5% of the organic solvent, and the mass of the surfactant is 1.6% of the aqueous solution; the pH value of the acid solution is 3.0, and its volume is 7.8% of the aqueous solution. II: Preparation of hydroxylated porous microspheres: The filtered silicon-oxygen porous microspheres were washed alternately with ethanol and pure water to remove organic solvents and polyethylene glycol; the washed and dried silicon-oxygen porous microspheres were added to a NaOH aqueous solution with a molar concentration of 4.6 mol / L, heated and stirred at 65°C for 1.5 hours, the solid microspheres were collected by centrifugation, washed with deionized water until neutral, and then dispersed in dilute hydrochloric acid at pH=2.8 for 50 minutes. The microspheres were then filtered out and repeatedly washed with water to remove residual ions, and dried at 40°C to obtain hydroxylated porous microspheres; The volume of NaOH aqueous solution used was 14 times the volume of the microspheres, and the volume of dilute hydrochloric acid used was 10 times the volume of the microspheres; the surface hydroxyl value of the hydroxylated porous microspheres was 4.3 mmol / g. III: Preparation of Aldehyde-Tylated Porous Microspheres: An anhydrous ethanol solution of trimethoxypropionaldehyde silane with a volume concentration of 1.6% was prepared. Glacial acetic acid was added to adjust the pH to 4.2, and the mixture was stirred at room temperature for 25 minutes. The dried hydroxylated porous microspheres were then added to the solution, and the temperature was controlled at 22°C for 45 minutes. The microspheres were filtered out and gently rinsed with anhydrous ethanol to remove the reaction monomers. They were then dried with nitrogen and allowed to stand at room temperature for 18 hours under nitrogen protection. After standing for another 22 minutes, the temperature was increased to 110°C, and the microspheres were obtained. The volume of the anhydrous ethanol solution of trimethoxypropionaldehyde silane was approximately 16 times the volume of the hydroxylated porous microspheres. The aldehyde group value on the surface of the aldehyde-tylated porous microspheres was 1.9 mmol / g. IV: Self-assembly of biomass-based microspheres: A 6.8% (w / w) aqueous solution of biomass polysaccharides was prepared. Glacial acetic acid was added to the solution to adjust the pH to 4.6. Aldehyde-modified porous microspheres were then added to the solution and incubated at 32°C. o The mixture was stirred at 220 rpm for 3.0 hours under temperature C, and the initial assembled microspheres were obtained by filtration. The volume of the added biomass polysaccharide aqueous solution was 8.5 times the volume of the microspheres. V: Solidification of biomass-based microspheres: The initially assembled microspheres were placed in acetone and stirred at 300 rpm to disperse them evenly. Glacial acetic acid was added to adjust the pH of the system to 4.0. Then, a small molecule aldehyde aqueous solution was slowly added dropwise and stirred for 2.6 hours. After the reaction was completed, the microspheres were filtered out, washed repeatedly with pure water, and dried at 55°C to obtain the final microsphere product. The volume ratio of the initially assembled microspheres to acetone was 1:9.2, the volume of the small molecule aldehyde aqueous solution was 8.4% of the volume of acetone, and the mass concentration of the small molecule aldehyde was 4.5%.

[0082] The molecular weight of the polyethylene glycol is 300.

[0083] The acid solution is an aqueous solution of hydrochloric acid.

[0084] The organic solvent is octane.

[0085] The surfactant is Tween 20.

[0086] The biomass polysaccharide is carboxymethyl chitosan, with a degree of substitution of 0.42 based on the proportion of substituted ethyl hydroxyl groups. It is a commercially available product.

[0087] The porous microspheres have a particle size between 220-280 μm and a porosity of 71%.

[0088] The biomass polysaccharide loading in the microspheres is 201.7 mg / g.

[0089] The small molecule aldehyde is glyoxal.

[0090] The final microsphere product has a particle size between 240 and 310 μm.

[0091] The final microsphere product has a compressive limit deformation of 64% and a compressive modulus of 0.94 MPa.

[0092] The microspheres were immersed in an aqueous solution of doxorubicin hydrochloride at a concentration of 20 mg / ml for 24 hours with a significant excess of solution. The drug concentration loaded on the microspheres reached 40 mg / ml (based on the volume of the microspheres), and the release time was 21 days, with a release ratio of 89%.

Claims

1. A process for the large-scale preparation of compression-resistant biomass-based microspheres, comprising the following steps: I: Preparation of silicon-oxygen porous microspheres: Prepare an aqueous solution containing tetramethoxysilane and polyethylene glycol. Add the aqueous solution and surfactant to an organic solvent and heat at 20-35°C. o At temperature C, the mixture is stirred at a speed of 250-500 rpm to form water-in-oil microspheres in an organic solvent. Then, an acid solution is gradually added dropwise to the organic solvent. Stirring is maintained for 1-2 hours to form silicon-oxygen porous microspheres through hydrolysis, which are then filtered. in, In the aqueous solution, the mass concentration of tetramethoxysilane is between 3-6%, and the mass concentration of polyethylene glycol is between 8-12%; the volume of the aqueous solution is between 15-20% of the organic solvent, and the mass of the surfactant is between 1.5-2.5% of the aqueous solution; the pH value of the acid solution is between 3-4, and the volume is between 6-10% of the aqueous solution. II: Preparation of hydroxylated porous microspheres: The filtered silicon-oxygen porous microspheres were washed alternately with ethanol and pure water to remove organic solvents and polyethylene glycol; the washed and dried silicon-oxygen porous microspheres were added to a NaOH aqueous solution with a molar concentration of 3-5 mol / L, heated and stirred at 60-80℃ for 0.5-1.5 hours, the solid microspheres were collected by centrifugation, washed with deionized water until neutral, and then dispersed in dilute hydrochloric acid with pH 2-4 for 30-60 minutes. The microspheres were then filtered out and repeatedly washed with water to remove residual ions. The microspheres were dried at a temperature below 60℃ to obtain hydroxylated porous microspheres. The volumes of NaOH aqueous solution and dilute hydrochloric acid used were between 10 and 20 times the volume of the microspheres; the surface hydroxyl value of the hydroxylated porous microspheres was between 3 and 6 mmol / g. III: Preparation of Aldehyde-Tylated Porous Microspheres: Prepare an anhydrous ethanol solution of trimethoxypropionaldehyde silane with a volume concentration between 0.5% and 2%. Adjust the pH to 4.0-5.0 with glacial acetic acid and stir at room temperature for 15-30 minutes. Then, add the dried hydroxylated porous microspheres into the solution and soak at 15-25°C for 30-60 minutes. Filter the microspheres and gently rinse them with anhydrous ethanol to remove the reaction monomers. Dry them with nitrogen and let them stand at room temperature for 12-24 hours under nitrogen protection. Then heat the solution to 100-115°C and let it stand for another 15-25 minutes to obtain aldehyde-tylated porous microspheres. The volume of the anhydrous ethanol solution of trimethoxypropionaldehyde silane is 12-20 times the volume of the hydroxylated porous microspheres. The aldehyde group value on the surface of the aldehyde-tylated porous microspheres is between 1.5-3 mmol / g. IV: Self-assembly of biomass-based microspheres: Prepare a 5-10% (w / w) aqueous solution of biomass polysaccharides. Adjust the pH to 4.0-5.0 by adding glacial acetic acid. Add aldehyde-modified porous microspheres to the solution and incubate at 25-40°C. o Stir at 150-300 rpm for 2-4 hours under temperature C, and filter to obtain initially assembled microspheres; wherein, the volume of biomass polysaccharide aqueous solution added is between 6-10 times the volume of the microspheres; V: Solidification of biomass-based microspheres: The initially assembled microspheres are placed in acetone and stirred at 250-400 rpm to disperse them evenly. Glacial acetic acid is added to adjust the pH of the system to between 4.0 and 5.

0. Then, a small molecule aldehyde aqueous solution is slowly added dropwise and stirring is continued for 1.5-3 hours. After the reaction is complete, the microspheres are filtered out, washed repeatedly with pure water, and dried at 30-60℃ to obtain the final biomass-based microsphere product. The volume ratio of the initially assembled microspheres to acetone is between 1:5 and 1:10, the volume of the aqueous solution of small molecule aldehydes is between 5% and 10% of the volume of acetone, and the mass concentration of small molecule aldehydes is between 3% and 6%.

2. The large-scale preparation process of compression-resistant biomass-based gel microspheres according to claim 1, characterized in that, The biomass polysaccharide is a water-soluble biomass polysaccharide containing amino groups and its derivatives.

3. The large-scale preparation process of compression-resistant biomass-based microspheres according to claim 1, characterized in that, The molecular weight of the polyethylene glycol is between 200 and 600.

4. The large-scale preparation process of compression-resistant biomass-based microspheres according to claim 1, characterized in that, The silicon-oxygen porous microspheres have a particle size between 100-600 μm and a porosity between 45-75%.

5. The large-scale preparation process of compression-resistant biomass-based microspheres according to claim 1, characterized in that, The small molecule aldehydes are one of glutaraldehyde and glyoxal.

6. The large-scale preparation process of compression-resistant biomass-based microspheres according to claim 1, characterized in that, The acid solution is an aqueous solution of hydrochloric acid, oxalic acid, acetic acid, and sulfuric acid.

7. The large-scale preparation process of compression-resistant biomass-based microspheres according to claim 1, characterized in that, The organic solvent is one of cyclohexane, cyclohexanone, octane, liquid paraffin, and isopropyl palmitate.

8. The large-scale preparation process of compression-resistant biomass-based microspheres according to claim 1, characterized in that, The surfactant is one of span80, tween20, and glyceryl monooleate.

9. The large-scale preparation process of compression-resistant biomass-based microspheres according to claim 1, characterized in that, The biomass polysaccharide loading in the biomass-based microspheres is between 150-300 mg / g.

10. The large-scale preparation process of compression-resistant biomass-based microspheres according to claim 1, characterized in that, The biomass-based microspheres can be loaded with drugs by soaking them in a water-soluble drug solution.

Citation Information

Patent Citations

  • Titration method for measuring the content of hydroxyl groups on the surface of silica microspheres

    CN116242960B